Infectious bursal disease virus: case report and experimental studies in vaccinated and unvaccinated SPF chickens and commercial broiler chicks - H Scanavini Neto; NMK Ito; CI Miyaji; E de A Lima; S Okabayashi; ARA Corrêa; GC Eleutério; MA Zuanaze (Brazilian Journal of Poultry Science, 2004)
IBDV Gm 11 (Simbios eleven-molecular group) has been detected since 1997 in many farms of commercial broilers and layers causing high mortality (2 to 15%) and severe macro and microscopic damage in cloacal bursae, spleen, thymus, kidney and liver. Five serial passages of 2050/97-Gm 11 IBDV sample by CAM route in SPF chicken's embryonated eggs did not elicit increased embryo mortality. High mortality (100%) of 21 day-old SPF leghorn chickens and severe bursal and splenic lesions were seen from 24 up to 48 hours after eye-drop inoculation of 2050/97 strain (50 mL of 10-2 dilution of 10% bursae homogenate). Mortality was not detected when vaccinated SPF and broiler chickens were inoculated. One dead bird was found among ten challenged unvaccinated broilers. Variations in the intensity of cloacal bursae injury and spleen response were found between unvaccinated and vaccinated broiler chickens. IBDV antibodies were detected by ELISA test in almost all vaccinated SPF chickens before challenge while low number of commercial vaccinated and unvaccinated broilers were serologically positive (0 to 3 birds in 18). Increasing IBDV antibody titers were detected after challenge with 2050/97 strain and highest GMTs were found in broilers. It was concluded that 2050/97 strain is a highly virulent IBDV and SPF leghorn chickens immunized with BV8 intermediate vaccine strain were resistant to the challenge. Increasing susceptibility was found from experimental groups of unvaccinated broilers to vaccinated broilers and to unvaccinated SPF birds. It is discussed that passive immunity was involved in the rate of protection of challenged unvaccinated broiler and in the immune response impairment after vaccination of broilers chicks. The use of a constant virus suspension with known potency to challenge the experimental birds was suitable to evaluate vaccination efficacy. Evaluation of bursal and splenic responses at early and delayed time after challenge were useful to estimate vaccination efficacy and field interactions.